Ethnomedicinal Uses of Plants by Major Ethnic Tribes in Terai Districts of Nepal - Mahamad Sayab Miya; Sachin Timilsina; Asmit Neupane (Hasanuddin University, 2021)
Indigenous communities and tribes of Nepal have been using medicinal plants for the treatment of several diseases or ailments since their origin. Various studies were conducted in the Terai region of Nepal regarding the pharmacological, ethnobotanical, and medicinal importance of plant species. This study aims to compile information on ethnomedicinal uses of plants by major ethnic groups in the Terai districts of Nepal. A total of 35 published documents based on ethnomedicinal uses of several medicinal plants in Terai of Nepal till 2020 A.D. were accessed for the study from online portals like Research Gate, Scopus, and Google Scholar. A total of 300 plant species from 98 families were documented which are used for the treatment of 120 diseases or ailments by the 8 ethnic groups of 6 terai districts. Leaf of plants is found to be used for the treatment of maximum number of diseases (72). Plants from families like Fabaceae, Malvaceae, Poaceae, etc. were used for the treatement of diseases like Diabetes, jaundice, syphilis, gastritis and other wounds, fractures along mental disorders. Indigenous knowledge and ethnomedicinal importance of different plant species must be explored, documented, and passed through different generations which could widen the scope of modern herbal medicine science.